Seven new synonyms within the genus Onthophagus (Coleoptera: Scarabaeidae) from the Oriental Region - Tarasov, Sergey I. (Zootaxa, 2010)
Examination of the type material of the Oriental representatives of the genus Onthophagus Latreille, 1802 (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini) deposited at the Natural History Museum in London, National Museum of Natural History in Paris, Museum of Natural History in Basel and National Museum in Prague revealed seven new synonyms. The names synonymized herein were described as separate species mainly for two reasons. The first reason owes to the insufficient knowledge of entire Onthophagus diversity from Oriental Region and the fact that authors describing new species did not check the type material or even original descriptions for already described taxa. The following synonymized species were likely described due to this oversight: O. anamalaiensis Balthasar, 1974; O. chulapornus Masumoto, Ochi & Hanboonong, 2008; O. demaak Masumoto, 1989; O. jucundus Arrow, 1931; O. laosensis Frey, 1971; and O. parvidens Frey, 1971. The second reason is the great range of intraspecific variation of such allometric characters as shape of head, horns and pronotum in Onthophagus. Therefore, detailed examination of the external characters for the large series of specimens, and careful study of male genitalia are required for reliable species identification. Unfortunately, this was not the case for many new species descriptions. In particular, O. perroti Paulian, 1978, was described as a species but actually only represents the minor form of O. orientalis Harold, 1868. The lectotype of O. gracilipes is designated in order to preserve the stability of zoological nomenclature.